Matrix-Assisted Laser Desorption Ionization–Time of Flight Mass Spectrometry-Based Functional Assay for Rapid Detection of Resistance against β-Lactam Antibiotics - Sparbier, Katrin (American Society for Microbiology, 2012)
Resistance against β-lactam antibiotics is a growing challenge for managing severe bacterial infections. The rapid and cost-efficient determination of β-lactam resistance is an important prerequisite for the choice of an adequate antibiotic therapy. β-Lactam resistance is based mainly on the expression/overexpression of β-lactamases, which destroy the central β-lactam ring of these drugs by hydrolysis. Hydrolysis corresponds to a mass shift of +18 Da, which can be easily detected by matrix-assisted laser desorption ionization–time of flight mass spectrometry (MALDI-TOF MS). Therefore, a MALDI-TOF MS-based assay was set up to investigate different enterobacteria for resistance against different β-lactam antibiotics: ampicillin, piperacillin, cefotaxime, ceftazidime, ertapenem, imipenem, and meropenem. β-Lactamases are enzymes that have a high turnover rate. Therefore, hydrolysis can be detected by MALDI-TOF MS already after a few hours of incubation of the bacteria to be tested with the given antibiotic. The comparison of the MS-derived data with the data from the routine procedure revealed identical classification of the bacteria according to sensitivity and resistance. The MALDI-TOF MS-based assay delivers the results on the same day. The approved routine procedures require at least an additional overnight incubation.